Organization Studies: A Space for Ideas, Identities and Agonies - Gabriel, Yiannis (Organization studies, 2010)
In this piece I argue that Organization Studies, like other academic journals, is not a sovereign subject able to chart its own path and make sovereign decisions on its strategy and direction. Instead, the journal is seen as embedded in complex networks of institutions and practices over which the editorial team has limited control; chief among them are the conventions of peer review, the proliferation of academic journals, the escalating pressures on academics to publish and the ceaseless struggle to improve ranking and citations. A useful way of looking at the journal is as a place where, following different institutional practices, ideas arrive, settle and meet each other, sometimes fight it out or, more often than not, decide to coexist in a civilized and polite way. Like the spaces of large cities, journals too become spaces crucial for the formation of individual and group identities, something that is accompanied by much agonizing about quality, acceptance, purity, contamination and even annihilation. The paper concludes with some reflections on the ethic of rational critique, at once the bedrock of academic discourse but also capable of inflicting much damage and of prematurely closing promising lines of inquiry. The author proposes that this ethic must be complemented by an ethic of care which stems from a recognition of fallibility and limits to our rationality. An ethic of care must inform not only the interactions among a journal’s different stakeholders but may spread to an attitude of stakeholders towards the journal itself, an attitude that approaches the journal as a valued intellectual space to be nurtured and cared for.